The Relationship between Cultural Control, Generational Differences, and Organizational Efficiency - Ria Sandra Alimbudiono; Hubert Sebastian Tandianto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to understand how intergenerational cultural control is implemented to improve organizational efficiency in a company where the majority of employees are Generation Z. The primary focus lies in exploring the differences in values, expectations, and communication styles between management (mostly millennials) and Gen Z staff, as well as the impact of these differences on compliance, motivation, and employee retention. This research adopts a qualitative case study approach using in-depth interviews with seven informants, consisting of both current and former employees. The analysis centers on three key elements of cultural control: code of conduct, group rewards, and interorganizational transfer. The findings reveal gaps in understanding organizational rules, perceptions of unfairness in the reward system, and the emergence of unmanaged informal communication cultures. These factors contribute to high turnover rates and declining organizational efficiency. The study also finds that Gen Z values transparency, work-life balance, and personalized appreciation, while millennial managers tend to rely on spontaneous and flexible approaches that do not fully align with the needs of younger employees. This research recommends improving the feedback system, establishing objective performance indicators, and strengthening healthy intergenerational communication channels as strategies to build a more adaptive and sustainable organizational culture.